SDGs 9: The Role of PT Adhi Karya in Sustainable Infrastructure Development - Rizki, Nevanda Julya; Bhayangkara, Ida Bagus Ketut (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Sustainable development is the initial step in improving community welfare. This step will help communities break free from the cycle of poverty. One of the sustainable development programs is the Sustainable Development Goals (SDGs). The SDGs consist of 17 pillars that serve as principles for achieving community prosperity. One of them is the 9th principle, which discusses the industry, innovation, and infrastructure sector. This 9th pillar will enhance services across various sectors of community life, thereby contributing to the realization of a prosperous society. This analysis uses a qualitative descriptive method, in which the researcher examines articles and journals from previous studies. The object of this research is PT Adhi Karya (Persero) Tbk, as the company operates in the infrastructure sector and has contributed significantly to the development of state-owned facilities to improve community welfare.